Copper-silver alloy catalyst and preparation and application thereof
Copper-silver alloy catalyst was prepared by sodium borohydride reduction method, and the catalytic activity and selectivity were improved by using Cu-Ag heterogeneous interface, which solved the reduction of active sites and hydrogen evolution reactions of existing copper-based catalysts during electrocatalyzed acetylene semihydrogenation process. Serious problems have achieved efficient and stable ethylene production.
Patent Information
- Application Number
- CN202411512751.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-10-28
AI Technical Summary
The existing copper-based catalysts have high surface energy in the electrocatalytic acetylene semihydrogenation process, resulting in agglomeration and reduced active sites, and are prone to competitive hydrogen evolution side reactions under high current density, reducing the selectivity of ethylene and Faraday efficiency.
Copper-silver alloy catalyst was prepared by sodium borohydride reduction method, and metal silver was introduced to form a rich Cu-Ag heterointerface, changing the electronic structure of the catalyst and the binding energy of the reaction intermediate, thereby improving catalytic activity and selectivity.
The intrinsic performance and electrocatalytic activity of the catalyst are achieved under simple and effective methods, and the catalytic performance and Faraday efficiency of acetylene reduction to ethylene are significantly improved, especially at high current density, which can maintain efficient conversion.
Smart Images

Figure CN119465253A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of alloy material preparation, and in particular to a copper-silver alloy catalyst and its preparation and application. Background Art
[0002] Among petrochemical products, ethylene, propylene, butadiene, benzene, toluene and xylene are important basic raw materials and are collectively known as "trienes" and "triphenylenes". Ethylene is an important commercial raw material for the production of polymers. Its products account for more than 75% of fossil products and play an important role in the national economy. According to a report by GlobalData, global ethylene demand will increase from 201 million tons / year in 2020 to 299 million tons / year in 2025, an increase of 49%. my country will also lead the growth of ethylene production capacity in Asia by 2025.
[0003] Petroleum steam cracking is currently the main process for producing ethylene, but the production process consumes a large amount of fossil fuels, which is harmful to the environment and not conducive to sustainable development. Since the 1950s, the thermal catalytic method for producing ethylene has gradually attracted people's attention. This method uses metal palladium as a catalyst and can achieve an acetylene conversion rate of more than 90% and an ethylene selectivity of 85% at 200°C. However, the cost of the precious metals used in this method is relatively high, and the ideal acetylene conversion rate can only be achieved when the reaction temperature is above 100°C. In addition, whether in industry or in the laboratory, it is necessary to add excess hydrogen during the reaction process, which increases the operational risk and reduces the selectivity of acetylene to ethylene. Therefore, people try to use green, clean and sustainable electrocatalytic methods to achieve efficient conversion of acetylene to ethylene. Through electrocatalytic means, water is used as a proton source to achieve hydrogenation reduction of raw materials at room temperature. This has been proven to be feasible and economical by many reports. With the continuous development of electrocatalytic reaction devices, the emergence of devices such as flow cells has solved the mass transfer problem of acetylene gas raw materials in aqueous solution. Acetylene gas that is insoluble in water is also expected to be able to use water protons to achieve selective hydrogenation to ethylene. Based on this, electrocatalytic acetylene reduction to ethylene has attracted widespread attention.
[0004] According to the different types of metal atoms in the active center, the metal-based catalysts currently used in the electrocatalytic semi-hydrogenation of acetylene can be divided into precious metal catalysts and non-precious metal catalysts. Precious metal catalysts represented by platinum have good performance in the electrocatalytic reduction of acetylene to ethylene, but their high price limits their industrial application. Recent studies have found that copper-based catalysts with low price and good conductivity also show good performance in the electrocatalytic semi-hydrogenation of acetylene. The surface of copper-based catalysts, especially the copper (111) crystal plane, has high ethylene adsorption energy and low ethylene desorption energy. While ensuring sufficient adsorption of the reactant acetylene, the product ethylene can be removed from the catalyst surface in time to prevent excessive reduction of acetylene to methane, greatly improving the catalytic activity and selectivity of acetylene reduction to ethylene. However, copper-based catalysts such as copper nanoparticles are prone to agglomeration during the reaction due to their high surface energy, resulting in a reduction in active sites, which reduces the activity and stability of the catalyst at high currents. In addition, in the process of electrocatalytic semi-hydrogenation of acetylene, the "proton-deficient" microenvironment at low current density is more conducive to the formation of C4 byproducts, reducing the selectivity of ethylene. At the same time, in aqueous electrolytes, especially at high reduction current density, a strong side reaction leading to competitive hydrogen evolution will occur, reducing the Faradaic efficiency of ethylene. Therefore, it is currently difficult to design a catalyst with a simple preparation process and high yield, which has highly active reaction sites and can inhibit carbon-carbon coupling and over-hydrogenation.
[0005] At present, people try to modify copper catalysts by various methods such as doping and compounding, thereby inhibiting competitive hydrogen evolution reaction and excessive hydrogenation reaction, thereby improving the catalytic activity and selectivity of copper-based catalysts for electrocatalytic acetylene semi-hydrogenation. For example, in the Chinese patent document with patent number CN115976548A, in order to prepare a supported metal phthalocyanine compound electrode, the method first disperses the metal phthalocyanine compound and the carrier in DMF under ultrasonic conditions, then mixes and stirs the metal phthalocyanine compound solution and the carrier solution, treats with plasma, and then filters, washes, and dries after the treatment. The obtained catalyst and nafion solution are poured into an organic solvent, and ultrasonic treatment is performed to obtain a slurry; the cut electrode material is washed; the slurry is evenly applied to the electrode material, and an infrared lamp is used to irradiate the solution until it is completely dried to obtain a supported metal phthalocyanine compound electrode. This method can achieve high selectivity and high stability of acetylene semi-hydrogenation under mild conditions, but the preparation process is relatively complicated. Therefore, a simpler and more effective method is needed to improve the intrinsic performance and electrocatalytic activity of the catalyst. Summary of the invention
[0006] Based on the above problems in the prior art, the present invention intends to provide a catalyst to improve the intrinsic performance and electrocatalytic activity of the catalyst in a simple and effective way, and to achieve high selectivity and high stability in the electrocatalytic semi-hydrogenation of acetylene to produce ethylene.
[0007] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical scheme.
[0008] A copper-silver alloy catalyst was prepared by a simple sodium borohydride reduction method. By introducing metallic silver into the copper base, a rich Cu-Ag heterogeneous interface was formed in the catalyst. These heterogeneous interfaces provide a large number of reactive sites. At the same time, the heterogeneous metal composite changes the electronic structure of the catalyst surface, so that when the catalyst is used in the electrocatalytic acetylene reduction reaction to produce ethylene, the binding energy of the key reaction intermediates *C2H3 and the like changes, thereby improving the catalytic performance of the electrocatalytic acetylene semi-hydrogenation to produce ethylene. More specifically, the technical solution provided by the present invention is as follows.
[0009] The present invention firstly provides a method for preparing a copper-silver alloy catalyst, which can obtain a copper-silver alloy catalyst with high electrocatalytic acetylene-to-ethylene activity through a simple sodium borohydride reduction method.
[0010] A method for preparing a copper-silver alloy catalyst comprises the following steps:
[0011] (1) adding copper nitrate and silver nitrate into deionized water to prepare an aqueous solution containing copper nitrate and silver nitrate and continuously stirring;
[0012] (2) preparing sodium borohydride solution as a reducing agent;
[0013] (3) adding the sodium borohydride solution of step 2) dropwise to the aqueous solution containing copper nitrate and silver nitrate of step 1) to carry out a reduction reaction, and the reduction product precipitates from the solution;
[0014] (4) The reduction product obtained in step (3) was washed with deionized water and anhydrous ethanol, filtered and dried in a vacuum oven at 60° C. for 12 h, taken out and ground to obtain a copper-silver alloy catalyst. The obtained catalyst was a gray-green powder.
[0015] More specifically, in step (1), the molar concentration of copper nitrate in the aqueous solution is 0.039-0.124 mol / L, the molar concentration of silver nitrate in the aqueous solution is 0.031-0.116 mol / L, and the molar ratio of copper nitrate to silver nitrate is 4:1-1:3. The copper-silver alloy catalyst prepared under these conditions, when applied to the electrocatalytic production of ethylene from acetylene, can further improve the catalytic activity and selectivity of the main product ethylene while ensuring good performance in inhibiting hydrogen evolution. If the proportion of silver in the prepared copper-silver alloy catalyst is too low, the change in the electronic structure of the catalyst surface is not obvious, and the catalytic activity and selectivity cannot be improved; if the proportion of silver is too high, the competitive hydrogen evolution reaction may be aggravated.
[0016] The stirring in step (1) is preferably performed at a speed of 600-1000 rpm.
[0017] The concentration of the sodium borohydride solution in step (2) is 1-5 mol / L. Excessive sodium borohydride can ensure that the metal ions are fully reduced to zero-valent metal elements and precipitate.
[0018] In step (3), in order to ensure that the reduction reaction is fully carried out, the reduction reaction solution is continuously stirred throughout the process while the sodium borohydride solution is added dropwise, and the stirring speed is 600-1000rpm. A relatively large rotation speed can ensure that the copper ions and silver ions in the solution fully react with the sodium borohydride, so that copper and silver are gradually precipitated in the form of simple substances more uniformly. At the same time, after the sodium borohydride solution is added dropwise, the stirring at this speed is still maintained for about 10 minutes, and the continuous high-speed stirring ensures that the reaction is fully carried out.
[0019] The preparation principle of the copper-silver alloy catalyst prepared by the sodium borohydride reduction method provided by the present invention is as follows: copper nitrate and silver nitrate are dissolved in an aqueous solution, and the sodium borohydride solution is slowly added dropwise to the aqueous solution containing copper nitrate and silver nitrate under vigorous stirring conditions. With the addition of the sodium borohydride solution, the copper ions and silver ions in the solution react with it to gradually generate a metal element and precipitate. Vigorous stirring and the slow dripping speed of sodium borohydride ensure that the silver ions and copper ions in the solution are gradually and uniformly precipitated in the form of a metal element in a certain proportion. Finally, the product obtained after the reduction reaction is washed with deionized water and anhydrous ethanol, thoroughly dried in vacuum, and ground to finally obtain a copper-silver alloy catalyst.
[0020] The present invention also provides a copper-silver alloy catalyst prepared by the above method, wherein the microscopic morphology of the copper-silver alloy catalyst is a coral-like structure composed of a plurality of copper nanoparticles and silver nanoparticles, wherein the copper nanoparticles and the silver nanoparticles are evenly distributed. The copper-silver alloy catalyst is composed of two phases of Cu and Ag, and the molar ratio of copper to silver is 4.12:1-1:2.95.
[0021] Furthermore, the microscopic morphology of the copper-silver alloy catalyst is a coral-like structure composed of a plurality of nanoparticles; wherein the copper nanoparticles and the silver nanoparticles are uniformly dispersed, and the molar ratio of copper to silver in the components constituting the copper-silver alloy catalyst is 0.51:1.
[0022] The present invention also provides the use of the copper-silver alloy catalyst in the electrocatalytic production of ethylene from acetylene, as described below.
[0023] The copper-silver alloy catalyst of the present invention is attached to carbon paper as a working electrode, and its loading amount is 0.8-1.8 mg cm -2 , using 1 mol / L potassium hydroxide solution as the electrolyte, the electrolyte flow rate is 10 mL / min, Hg / HgO as the reference electrode, nickel foam as the counter electrode, forming a three-electrode system to carry out the electrocatalytic acetylene to ethylene reaction in a fluid electrolysis cell.
[0024] The present invention prepares the copper-silver alloy catalyst by a simple sodium borohydride reduction method, introduces metallic silver into a copper-based catalyst, and forms a copper-silver alloy catalyst by compounding with copper. The combination of the two regulates the electronic structure of the catalytic material and the binding energy of the reaction intermediates in the process of electrocatalytic acetylene to ethylene reaction, and simultaneously forms a rich Cu-Ag heterogeneous interface, thereby providing a large number of active sites and improving the catalytic activity and selectivity of electrocatalytic acetylene to ethylene.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] (1) A copper-silver alloy catalyst was prepared by a simple sodium borohydride reduction method. The preparation method is simple, efficient, reproducible, and suitable for industrial production.
[0027] (2) The present invention prepares a copper-silver alloy catalyst by a simple sodium borohydride reduction method, in which copper and silver nanoparticles are uniformly compounded together, and has good conductivity and electrocatalytic potential. For example, the catalyst has a large current density and a low overpotential in the test potential range, showing excellent electrocatalytic potential.
[0028] (3) The present invention prepares a copper-silver alloy catalyst by a simple sodium borohydride reduction method, so that metallic silver is successfully introduced into the copper-based catalyst, forming a rich Cu-Ag heterogeneous interface, providing a large number of active sites, changing the electronic structure of the catalyst such as the electron cloud density and the binding energy of the reaction intermediates such as *C2H3 in the process of electrocatalytic acetylene reduction to ethylene, thereby improving the catalytic performance of electrocatalytic acetylene semi-hydrogenation to ethylene. For example, at a current density of 100 mA cm -2 When the current density is 500 mA cm -2 When compared with the nano-copper catalyst, its ethylene Faraday efficiency increased from 92.2% to 97.1%.
[0029] (4) A copper-silver alloy catalyst prepared by the present invention has good stability even at 600 mA cm -2 Even at a high current density, its Faradaic efficiency of acetylene to ethylene still reaches 89.2%, reflecting its potential for industrial application.
[0030] (5) The present invention uses clean and renewable electricity as energy, and can achieve efficient conversion of acetylene to ethylene without increasing temperature or pressure. In addition, the reaction system uses water as a hydrogen source, and does not require the addition of hazardous hydrogen, which is in line with the concept of green, environmentally friendly and sustainable development. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1This is the SEM image of the copper-silver alloy catalyst prepared in Example 1.
[0032] Figure 2 This is the TEM image of the copper-silver alloy catalyst prepared in Example 1.
[0033] Figure 3 The XRD diagrams of the catalysts prepared in Example 1, Comparative Example 1 and Comparative Example 2 are shown.
[0034] Figure 4 The electrochemical polarization curves of the catalysts prepared in Example 1, Comparative Example 1 and Comparative Example 2 in a three-electrode reaction cell and 1M potassium hydroxide electrolyte.
[0035] Figure 5 This is a diagram of the ethylene Faraday efficiency of the catalysts prepared in Example 1 and Comparative Examples 1 and 2 in a three-electrode reaction cell and 1M potassium hydroxide electrolyte.
[0036] Figure 6 This is a Faraday efficiency diagram of 1,3-butadiene of the catalysts prepared in Example 1 and Comparative Examples 1 and 2 in a three-electrode reaction cell and 1M potassium hydroxide electrolyte.
[0037] Figure 7 This is a diagram of the hydrogen Faraday efficiency of the catalysts prepared in Example 1 and Comparative Examples 1 and 2 in a three-electrode reaction cell and 1M potassium hydroxide electrolyte. DETAILED DESCRIPTION
[0038] The present invention will be further described below in conjunction with the accompanying drawings and specific examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturer.
[0039] Example 1
[0040] A preparation step of a copper-silver alloy catalyst:
[0041] Step 1: Weigh 0.1000g of copper nitrate and 0.1406g of silver nitrate on an electronic balance, that is, the molar ratio of copper nitrate to silver nitrate is 1:2, and fully dissolve them in 8ml of deionized water under magnetic stirring at 600-1000rpm.
[0042] Step 2: Weigh 0.3783 g of sodium borohydride on an electronic balance and dissolve it in 2 ml of deionized water, i.e. a concentration of 5 mol / L.
[0043] Step 3: slowly add the prepared sodium borohydride solution dropwise to the aqueous solution containing silver nitrate and copper nitrate, and while adding, continuously stir the reaction solution with magnetic force at a speed of 800 rpm. After the sodium borohydride solution is added dropwise, stir at this speed for about 10 minutes until the reduction reaction is completed. Continuous stirring at a high speed ensures that the reduction reaction is fully carried out and copper and silver are uniformly precipitated, and finally a composite precipitate with uniformly distributed copper-silver nanoparticles is obtained.
[0044] Step 4: The precipitate in step 3 is washed with deionized water and anhydrous ethanol, filtered and dried in a vacuum oven at 60° C. for 12 h, taken out and ground to obtain a copper-silver alloy catalyst, the catalyst powder of which is gray-green.
[0045] Example 2
[0046] A preparation step of a copper-silver alloy catalyst:
[0047] Step 1: Weigh 0.2400 g of copper nitrate and 0.04218 g of silver nitrate on an electronic balance, that is, the molar ratio of copper nitrate to silver nitrate is 4:1, and fully dissolve them in 8 ml of deionized water under magnetic stirring.
[0048] Step 2: Weigh 0.3000 g of sodium borohydride on an electronic balance and dissolve it in 2 ml of deionized water.
[0049] Step 3: slowly add the prepared sodium borohydride solution dropwise to the aqueous solution containing silver nitrate and copper nitrate, and while adding, continuously stir the reaction solution magnetically at a speed of 900 rpm. After the sodium borohydride solution is added dropwise, stir at this speed until the reduction reaction is completely completed to obtain a precipitate.
[0050] Step 4: The precipitate in step 3 is washed with deionized water and anhydrous ethanol, filtered and dried in a vacuum oven at 60° C. for 12 h, taken out and ground to obtain a gray-green powdery copper-silver alloy catalyst.
[0051] Example 3
[0052] A preparation step of a copper-silver alloy catalyst:
[0053] Step 1: Weigh 0.1500 g of copper nitrate and 0.1055 g of silver nitrate on an electronic balance, that is, the molar ratio of copper nitrate to silver nitrate is 1:1, and fully dissolve them in 8 ml of deionized water under magnetic stirring.
[0054] Step 2: Weigh 0.3000 g of sodium borohydride on an electronic balance and dissolve it in 2 ml of deionized water.
[0055] Step 3: slowly add the prepared sodium borohydride solution dropwise into the aqueous solution containing silver nitrate and copper nitrate, and at the same time, fully carry out reduction reaction under magnetic stirring at a speed of 600 rpm to obtain a precipitate.
[0056] Step 4: The precipitate in step 3 is washed with deionized water and anhydrous ethanol, filtered and dried in a vacuum oven at 60° C. for 12 h, taken out and ground to obtain a copper-silver alloy catalyst.
[0057] Example 4
[0058] A preparation step of a copper-silver alloy catalyst:
[0059] Step 1: Weigh 0.0750 g of copper nitrate and 0.1582 g of silver nitrate on an electronic balance, that is, the molar ratio of copper nitrate to silver nitrate is 1:3, and fully dissolve them in 8 ml of deionized water under magnetic stirring.
[0060] Step 2: Weigh 0.0756 g of sodium borohydride on an electronic balance and dissolve it in 2 ml of deionized water.
[0061] Step 3: slowly add the prepared sodium borohydride solution dropwise into the aqueous solution containing silver nitrate and copper nitrate, and at the same time, fully carry out reduction reaction under magnetic stirring at a speed of 1000 rpm to obtain a precipitate.
[0062] Step 4: The precipitate in step 3 is washed with deionized water and anhydrous ethanol, filtered and dried in a vacuum oven at 60° C. for 12 h, taken out and ground to obtain a gray-green powdery copper-silver alloy catalyst.
[0063] The copper-silver alloy catalysts prepared in each embodiment were subjected to microscopic morphology and composition analysis. Through SEM and TEM analysis, the copper-silver alloy catalysts prepared in each embodiment showed a coral-like structure composed of a plurality of copper nanoparticles and silver nanoparticles in microscopic morphology, in which the copper nanoparticles and the silver nanoparticles were evenly distributed. Figure 1 and Figure 2 The SEM and TEM images of the copper-silver alloy catalyst prepared in Example 1 are shown in FIG. Figure 1 It can be seen from the figure that the copper-silver alloy catalyst prepared in Example 1 is composed of nanoparticles, and its microscopic morphology is relatively regular; Figure 2 It can be seen that the prepared copper-silver alloy catalyst has a coral-like structure composed of several nanoparticles.
[0064] Through XRD detection, it is confirmed that the copper-silver alloy catalyst prepared in each embodiment is composed of Cu and Ag, wherein the main exposed crystal surface of Cu is the Cu(111) crystal surface, and the main exposed crystal surface of Ag is the Ag(111) crystal surface. For example, Figure 3The XRD diagram of the copper-silver alloy catalyst prepared in Example 1 is recorded in the figure. It can be seen from the figure that the main components of the copper-silver alloy catalyst prepared in Example 1 are Ag and Cu. After further testing, the copper-silver molar ratio of the components of the copper-silver alloy catalyst prepared in each embodiment basically satisfies the molar ratio of the copper-silver raw materials added when preparing the copper-silver catalyst within the range of 4:1-1:3. The corresponding test results in each embodiment are basically consistent with the ratio of raw materials added. For example, in the copper-silver alloy catalyst prepared in Example 1, the test results show that the copper-silver molar ratio is 0.51:1; in the copper-silver alloy catalyst prepared in Example 2, the copper-silver molar ratio is: 4.12:1; in the copper-silver alloy catalyst prepared in Example 3, the copper-silver molar ratio is: 1.04:1; in the copper-silver alloy catalyst prepared in Example 4, the copper-silver molar ratio is 1:2.95. This also confirms that the reduction reaction in the preparation process is very sufficient.
[0065] The copper-silver alloy catalysts prepared in each embodiment were applied to the electrocatalytic semi-hydrogenation of acetylene to produce ethylene, and all showed excellent Faraday efficiency and high ethylene specific selectivity. The following Application Example 1 is a specific application of the copper-silver alloy catalyst prepared in Example 1.
[0066] Application Example 1
[0067] The copper-silver alloy catalyst prepared in Example 1 is used as a cathode material for preparing ethylene by electrocatalytic semi-hydrogenation of acetylene.
[0068] Step 1: Use an analytical balance to weigh 10 mg of the catalyst prepared in Example 1, and at the same time take 100 μL of isopropanol and 20 μL of 0.5 wt.% Nafion solution, mix the three evenly, and put them into a sample bottle for ultrasonication for 2 hours.
[0069] Step 2: Cut out 2×2cm 2 Carbon paper, stick polytetrafluoroethylene tape around it, leaving 1×1cm 2 Measure 100 μL of the catalyst solution prepared in step 1 and add it dropwise to a 1×1 cm 2 The catalyst loading on the carbon paper was 1 mg cm -2 , dried at room temperature or under infrared light, and used as a working electrode.
[0070] Step 3: Use Hg / HgO as the reference electrode and nickel foam as the counter electrode. Together with the working electrode, they form a three-electrode system and are placed in a fluid electrolysis cell. Use 1M potassium hydroxide as the electrolyte solution. Tests are performed at different current densities. The yields of product ethylene and by-product 1,3-butadiene are analyzed by gas chromatography.
[0071] Application Example 2
[0072] The copper-silver alloy catalyst prepared in Example 1 is used as a cathode material for electrocatalytic acetylene semi-hydrogenation to produce ethylene. The catalyst loading in this application example is 0.8 mg cm -2 , the rest is exactly the same as Application Example 1.
[0073] Application Example 3
[0074] The copper-silver alloy catalyst prepared in Example 1 is used as a cathode material for electrocatalytic acetylene semi-hydrogenation to produce ethylene. The catalyst loading in this application example is 1.8 mg cm -2 , the rest is exactly the same as Application Example 1.
[0075] In addition to the application of the copper-silver alloy catalyst in Example 1, the inventors also used the copper-silver alloy catalysts prepared in other examples as cathode materials for electrocatalytic acetylene semi-hydrogenation to produce ethylene. The application conditions were consistent with those in Example 1-3, and the loading amount was preferably 0.8-1.8 mg cm -2 When the loading amount is too low, there are fewer catalytic active sites and the hydrogen evolution side reaction is more serious; when the loading amount is too high, more acetylene is adsorbed on the catalyst surface and the active hydrogen is insufficient, which will lead to an increase in the carbon four byproduct.
[0076] The catalysts prepared in each embodiment were tested for their application effects under the conditions of the above application examples, showing that the catalysts had a catalyst activity of 0.8-1.8 mg cm -2 At a catalyst loading of , the catalytic performance and Faraday efficiency of the catalysts in each embodiment are comparable, and all exhibit excellent catalytic performance and ethylene Faraday efficiency. Taking the data of Application Example 1 as an example, Figure 4 It can be seen that the current density of the copper-silver alloy catalyst prepared in Example 1 at different potentials, the catalyst has a large current density in the tested potential range, reflecting its good conductivity and catalytic potential. Figure 5 It can be seen that the ethylene Faraday efficiency of the catalyst in Example 1 at different current densities is -2 When the ethylene Faraday efficiency reaches the highest, about 97.1%; Figure 6 It can be seen that the 1,3-butadiene Faraday efficiency of the catalyst at different current densities is about 1.02%, and the formation of the byproduct 1,3-butadiene in Example 1 is significantly suppressed compared with Comparative Example 1, thereby improving the selectivity of the product ethylene. Figure 7 It can be seen that the catalyst has a high conductivity at 100-500 mA cm -2 In the range of , the Faraday efficiency of hydrogen is less than 0.52% and the current density is 600 mA cm -2 When the hydrogen Faraday efficiency is 0.044%, it has good performance in inhibiting hydrogen evolution.
[0077] Comparative Example 1
[0078] A method for preparing a copper-based catalyst:
[0079] Step 1: Weigh 0.300 g of copper nitrate on an electronic balance and fully dissolve it in 8 ml of deionized water under magnetic stirring.
[0080] Step 2: Weigh 0.3783 g of sodium borohydride on an electronic balance and dissolve it in 2 ml of deionized water.
[0081] Step 3: slowly add the prepared sodium borohydride solution dropwise into the aqueous solution containing silver nitrate and copper nitrate, and fully carry out reduction reaction under magnetic stirring at a speed of 800 rpm to obtain a precipitate.
[0082] Step 4: The precipitate in step 3 is washed with deionized water and anhydrous ethanol, filtered and dried in a vacuum oven at 60°C for 12 hours, taken out and ground to obtain a copper-based catalyst. Figure 3 As shown in , it is shown that the component of the copper-based catalyst prepared in Comparative Example 1 is single substance Cu.
[0083] The copper-based catalyst prepared in Comparative Example 1 was applied to the electrocatalytic acetylene semi-hydrogenation to produce ethylene. The copper-based catalyst was used as the cathode material for the electrocatalytic acetylene semi-hydrogenation to produce ethylene. Except for the cathode material, the other method steps and parameters were the same as those in Application Example 1. Tests showed that Figure 4 Compared with the copper-silver alloy catalyst of Example 1, the copper-based catalyst of Comparative Example 1 has a lower current density in the test interval than the copper-silver alloy catalyst, and is significantly lower in conductivity and catalytic potential than the copper-silver alloy catalyst. Figure 5 The test results show that the highest Faraday efficiency of electrocatalytic acetylene semi-hydrogenation to ethylene using the copper-based catalyst of Comparative Example 1 as the cathode material is about 92.2%, which is significantly lower than that of Example 1. Figure 6 As shown in Figure 2, carbon-carbon coupling is more intense at low current density, and more 1,3-butadiene by-products are generated. -2 The Faradaic efficiency of electrocatalytic acetylene semi-hydrogenation to 1,3-butadiene was about 34.5%. Figure 7 It can be seen that the catalyst has a high conductivity at 100-500 mA cm -2 In the range of , the Faraday efficiency of hydrogen is lower than 3.41%, and it also has good performance in inhibiting hydrogen evolution, but the current density is 600mAcm -2 When the hydrogen Faraday efficiency is 16.5%, it is significantly higher than that of the embodiment.
[0084] Comparative Example 2
[0085] A method for preparing a silver-based catalyst:
[0086] Step 1: Weigh 0.2109 g of silver nitrate on an electronic balance and fully dissolve it in 8 ml of deionized water under magnetic stirring.
[0087] Step 2: Weigh 0.3783 g of sodium borohydride on an electronic balance and dissolve it in 2 ml of deionized water.
[0088] Step 3: slowly add the prepared sodium borohydride solution dropwise into the aqueous solution containing silver nitrate and copper nitrate, and fully carry out reduction reaction under magnetic stirring at a speed of 800 rpm to obtain a precipitate.
[0089] Step 4: The precipitate in step 3 is washed with deionized water and anhydrous ethanol, filtered and dried in a vacuum oven at 60°C for 12 hours, taken out and ground to obtain a silver-based catalyst. Figure 3 As shown in , it is shown that the silver-based catalyst prepared in Comparative Example 2 contains single substance Ag.
[0090] The silver-based catalyst prepared in Comparative Example 2 was used in the electrocatalytic semi-hydrogenation of acetylene to produce ethylene. The copper-based catalyst was used as the cathode material for the electrocatalytic semi-hydrogenation of acetylene to produce ethylene. Except for the cathode material, the other method steps and parameters were the same as those in Application Example 1. Tests showed that Figure 4 Compared with the copper-silver alloy catalyst of Example 1, the silver-based catalyst of Comparative Example 2 has a lower current density in the test range than the copper-silver alloy catalyst, and is significantly lower in conductivity and catalytic potential than the copper-silver alloy catalyst. Figure 5 The test results show that the highest Faraday efficiency of electrocatalytic acetylene semi-hydrogenation to ethylene is about 65.9% when the silver-based catalyst of Comparative Example 2 is used as the cathode material, and its catalytic performance is significantly lower than that of Example 1; -2 In the current density range of 500 mA cm -2 The hydrogen Faradaic efficiency is 92.8% at 600 mA cm -2 When the hydrogen evolution side reaction is more intense, the hydrogen Faraday efficiency is further increased (such as Figure 7 ).
[0091] It should be noted that the specific implementation method described above provides a detailed description of the technical scheme and application results of the present invention. Please understand that the above embodiments are only the most preferred embodiments and are not used to limit the present invention. Modifications or equivalent substitutions made by relevant technical personnel within the core theoretical scope of the present invention should all fall within the protection scope of the present invention.
Claims
1. A copper-silver alloy catalyst, characterized in that: The copper-silver alloy catalyst consists of two phases of Cu and Ag, and the molar ratio of copper to silver is 4.12:1-1:2.
95.
2. A copper-silver alloy catalyst according to claim 1, characterized in that: The microscopic morphology of the copper-silver alloy catalyst is a coral-like structure composed of a plurality of copper nanoparticles and silver nanoparticles, wherein the copper nanoparticles and the silver nanoparticles are evenly distributed.
3. A copper-silver alloy catalyst according to claim 2, characterized in that: The molar ratio of copper to silver in the components constituting the copper-silver alloy catalyst is 0.51:
1.
4. A method for preparing a copper-silver alloy catalyst according to any one of claims 1 to 3, characterized in that: Includes steps: 1) adding copper nitrate and silver nitrate into deionized water to prepare an aqueous solution containing copper nitrate and silver nitrate and continuously stirring; 2) preparing sodium borohydride solution as a reducing agent; 3) adding the sodium borohydride solution of step 2) dropwise to the aqueous solution containing copper nitrate and silver nitrate of step 1) to carry out a reduction reaction, and the reduction product precipitates from the solution; 4) washing the product obtained in step 3) with deionized water and anhydrous ethanol, filtering and drying in a vacuum oven, taking out and grinding to obtain a copper-silver alloy catalyst.
5. The method for preparing a copper-silver alloy catalyst according to claim 4, characterized in that: In step 1), the molar concentration of copper nitrate in the aqueous solution is 0.039-0.124 mol / L, the molar concentration of silver nitrate in the aqueous solution is 0.031-0.116 mol / L, and the molar ratio of copper nitrate to silver nitrate is 4:1-1:
3.
6. The method for preparing a copper-silver alloy catalyst according to claim 4, characterized in that: The concentration of the sodium borohydride solution in step 2) is 1-5 mol / L.
7. The method for preparing a copper-silver alloy catalyst according to claim 4, characterized in that: In step 3), sodium borohydride solution is added dropwise under stirring at a stirring speed of 600-1000 rpm.
8. Use of a copper-silver alloy catalyst according to any one of claims 1 to 3, characterized in that: The copper-silver alloy catalyst is used for preparing ethylene by electrocatalytic reduction of acetylene and serves as a cathode material for the electrocatalytic acetylene reduction reaction.
9. The use of a copper-silver alloy catalyst according to claim 8, characterized in that: The copper-silver alloy catalyst is attached to carbon paper as a working electrode, potassium hydroxide solution is used as an electrolyte, Hg / HgO is used as a reference electrode, and nickel foam is used as a counter electrode to form a three-electrode system for electrocatalytic acetylene reduction reaction to prepare ethylene in a fluid electrolytic cell.
10. The use of a copper-silver alloy catalyst according to claim 9, characterized in that: The steps of applying the copper-silver alloy catalyst to electrocatalytic acetylene reduction to prepare ethylene are as follows: Step 1, taking the copper-silver alloy catalyst, isopropanol and Nafion solution and uniformly mixing them to form a catalyst solution; Step 2: Take the catalyst solution and add it dropwise onto the carbon paper to make the catalyst loading amount 0.8-1.8 mg cm -2 , and after drying, a working electrode is obtained; Step three, using Hg / HgO as a reference electrode, nickel foam as a counter electrode, and the working electrode together to form a three-electrode system placed in a fluid electrolytic cell, using 1M potassium hydroxide as an electrolyte solution, and performing an electrocatalytic acetylene reduction reaction to produce ethylene.
Citation Information
Patent Citations
Double-metal silver-copper nano-particle and application thereof
CN107233896A
Preparation and application of silver-copper alloy nanoparticle low-temperature ammoxidation catalyst
CN109692688A
Bimetallic porous silver-copper network structure nitrogen reduction catalyst and preparation method thereof
CN110560083A
Electrocatalytic acetylene hydrogenation reaction method
CN113026037A
Copper / silver alloy nano-catalyst as well as preparation method and application thereof
CN113578346A